Alternative News Media and Critique of Mainstream Journalism in India: The Case of OpIndia. Issue 8 (27th August 2022) - Chadha, Kalyani; Bhat, Prashanth
Abstract: "Alternative news media, " that explicitly position themselves against mainstream media have emerged as an increasingly visible aspect of media systems globally including in India. And although such media can espouse left/right political positions, in the Indian context, such outlets are supportive of right-wing politics of the ruling Hindu nationalist Bharatiya Janata Party (BJP). In this article—drawing on rhetorical approaches—we explore the efforts of OpIndia, the most-visited right-wing news site in India to critique and correct the country's mainstream news outlets through a textual analysis of 576 articles contained in the site's Media Fact Check section.